Penerapan Dynamic Lighting pada 2D Endless Runner Game menggunakan Visibility Polygon Computation - Arda Satata Fitriajie; Eriq Muhammad Adams Jonemaro; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
This study aims to develop dynamic lighting modules in video games with 2D environments that have endless runner types that use the principle of polygon visibility. One type of graphic effect that exists in video games is dynamic lighting, this effect is generally applied to 3D games where the effect can bring a realistic and immersive impression on the game being played. The implementation of dynamic lighting in 2D games in the previous study was implemented using a method used in 3D games, namely normal mapping, the technique is more commonly used in top-down games and game with isometric style, whereas in the game to be implemented polygon visibility techniques due to game perspective which is seen from the side. In this study, dynamic lighting will be implemented using the concept of polygon visibility because the light nature is the same as the vision concept that exists in the concept of polygon visibility in the flat two-dimensional polygon visibility in this study implemented using raycasting which is shot from a point and spreads like light where light represented by one ray object emitted by the module. Based on the above requirements, dynamic lighting modules will be implemented in 2D endless runner games that produce dynamic lighting modules that are implemented using raycasting that visualize polygon visibility and obtain 100% valid functional test results and fps performance testing of 2 test cases that get fps above 24.